2012
DOI: 10.5402/2012/375038
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Dysfunction in Children following Cardiac Bypass Surgery

Abstract: Background. Sensorineural hearing loss after procedures including extracorporeal circulation and hypothermia is greater than general population. Mild hypothermia has a protective role on cochlea; however, deep hypothermia may result in cochlear injury. This research aimed at assessing auditory function in children after open heart surgery in relation to different hypothermic techniques. Subjects and Methods. Forty children with acyanotic heart diseases who underwent open heart surgery were included: group I: t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…During cardiac surgeries whole-body hypothermia was applied. It was shown that the TEOAE and DPOAE response is dependent on the body core temperature [ 32 , 33 , 34 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…During cardiac surgeries whole-body hypothermia was applied. It was shown that the TEOAE and DPOAE response is dependent on the body core temperature [ 32 , 33 , 34 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…El Ganzoury et al . in 2012 compared normothermic and hypothermic ECC to assess hearing outcomes 24 . In this study, there was no overall significant change in audiometry.…”
Section: Resultsmentioning
confidence: 65%
“…Multiple potential pathophysiological mechanisms have been proposed for the development of SNHL after cardiac surgery 17,18,24,33–36 . The most discussed relate to hypoperfusion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations